Mindfulness-Based Cognitive Therapy for Treating Chronic Pain A Systematic Review and Meta-analysis. Issue 3 (16th March 2021) - Pei, Ju-Hong; Ma, Tong; Nan, Rui-Lin; Chen, Hai-Xia; Zhang, Ya-Bin; Gou, Lin; Dou, Xin-Man
ABSTRACT: Chronic pain is a significant public health problem with emotional and disabling factors, which may not completely respond to current medical treatments such as opioids. The systematic review and meta-analysis aimed to examine the effectiveness and safety of MBCT for patients with chronic pain. Database searches of PubMed, Medline, EMBASE, the Cochrane Library, PsycINFO, Web of Science, Scopus and CINAHL up to 15 October 2019. Included studies assessed with the Cochrane risk-of-bias tool. Eight RCTs involved 433 patients, including chronic low back pain, fibromyalgia, migraine, rheumatoid arthritis and mix etiology. MBCT intervention demonstrated a short-term improvement on depression mood [standardized mean difference −0.72; 95% confidence interval = −1.22 to −0.22, p = 0.005] compared with usual care and was associated with short-term improvement in mindfulness compared with non-MBCT [SMD 0.51; 95% CI = 0.01 to 1.01, p = 0.04]. Between-group differences in pain intensity, pain inference and pain acceptance were not signiﬁcant at short- or long-term follow-up. Compared to active treatments, MBCT intervention not found significant differences in either short- or long-term outcomes. MBCT showed short-term efficacious on depressed mood and mindfulness of chronic pain patients. Longer follow-ups, large sample and rigorous RCTs that can be best understand remaining uncertainties needed.